Theoretical analysis and experimental investigation of hysteretic performance of self-centering variable friction damper braces. (15th August 2020) - Wang, Yongwei; Zhou, Zhen; Xie, Qin; Huang, Linjie
Highlights: Variable friction dampers are incorporated with the post-tensioning technology. A novel flag-shape hysteretic curve is proposed. Post-yield stiffness of SC-VFD brace increases after the second activation. The experimental result and theoretical analysis considering the influence of tube length tolerance show same tendency. Abstract: Traditional buildings, even with normal self-centering energy dissipation (SCED) braces, might suffer from large deformations and high mode effects under an extremely strong earthquake, leading to a concentration of inter-story drift in upper floors. To satisfy the requirements of resilience, larger post-yield stiffness and higher energy dissipation, a novel brace with pretensioned basalt fiber-reinforced polymer (BFRP) tendons and variable friction dampers (VFDs) was developed, and this brace was termed the self-centering variable friction damper (SC-VFD) brace. The variable stiffness and sliding force of the VFD system were theoretically analyzed. This was followed by quasi-static experiments on two VFD and two SC-VFD braces with different parameters. The theoretical analysis and experimental results revealed the same tendencies, demonstrating the reliability and feasibility of SC-VFD braces. The hysteretic curve of the SC-VFD braces exhibited stable and normal flag-shape behavior before the second activation, while the hysteresis curve indicated a variable flag-shape behavior with second activation, variable friction force, and larger post-yield stiffness when the brace slid at slope section. Compared with the VFD brace, the SC-VFD brace had the same energy dissipation ability but less residual displacement and lower equivalent viscous damping ratio. More combinations of disc springs in series resulted in smaller axial forces and lowers post-yielding stiffness, thereby decreasing the energy dissipation capability.